Pemberdayaan UMKM Peyek Layyunda Desa Ngrimbi Melalui Digital Marketing - Satria Ardhana (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2023)
UMKM is the Layyunda Project which is located in Ngrimbi Village, Bareng District, Jombang Regency. UMKM Peanut Layyunda is an MSME that is engaged in making Peanut, Shrimp and Anchovy Projects. The UMKM Peyek Layyunda was founded in Jombang in 2019 with the owner, Mrs. Datis Safarotin. The brand "Layyunda" is the name of him and the son of the MSME owner. The characteristic that is reflected in Layyunda's Peyek is its crispness and the aroma of lime leaves which are the mainstay of this Layyunda's Peyek product. The method in this study uses observation techniques (observation), interviews, and evaluation. The intended target is a food product MSME business actor named Peyek Layyunda. The results of this study apply the use of digital marketing in the form of Instagram social media.